An Unusual Case of Cutaneous Pili Migrans in a 45-Day-Old Infant - Yang D; Zhu R; Yang X; Huang S; Guo M (Dove Medical Press, 2023)
Dingbin Yang,* Renheng Zhu,* Xuejun Yang, Shuqiong Huang, Menglu Guo Department of Dermatology, People's Hospital of Leshan, Leshan, 614000, People's Republic of China*These authors contributed equally to this workCorrespondence: Dingbin Yang, Department of Dermatology, People's Hospital of Leshan, No. 238, Baita Street, Leshan, 614000, People's Republic of China, Tel +86-15681383138, Email yangdingbin@163.comAbstract: Cutaneous Pili Migrans (CPM), a rare skin condition, is composed of hair fragments embedded in the skin epidermis and dermis after skin trauma or for unknown reasons. To the best of our knowledge, there are few reports on cases of CPM in which hair is exposed outside of the skin. Herein, we report an unusual and rare case of 45 days old Chinese male infant with CPM.Keywords: cutaneous pili migrans, creeping hair, burrowing hair